Nose to Brain Drug Delivery System: A Comprehensive Review - Kumar, Pankaj; Garg, Varun; Mittal, Neeraj (Drug Delivery Letters, 2020)
Nose to brain drug delivery system is an interesting approach to deliver a drug directly in the brain through the nose. Intranasal drug delivery is very beneficial because it avoids first-pass metabolism and achieves a greater concentration of drugs in the central nervous system (CNS) at a low dose. This delivery system is used for the treatment of various neurological disorders such as Parkinson's disease, Alzheimer's disease, schizophrenia, dementia, brain cancer, etc. To treat such types of diseases, different formulations like nanoparticles (NPs), microemulsions, in situ gel, etc. can be used depending on the physiochemical properties of the drug. In this review, some essential characteristics related to the delivery of nose to the brain and their possible obstacles are underlined, which include anatomy and physiology of nose to brain delivery. This review also summarizes innovations from the past three to five years.
Keywords: liposomes